The Environmental Impacts of Agricultural Intensification - Garcia, Alberto (CGIAR Advisory Services, 2020)
Agricultural intensification is necessary to meet growing global food demand, but it has potential environmental costs. Some activities associated with intensification, including increased use of fertilizer and other chemical inputs, are documented to have direct negative impacts on air and water quality, soil fertility, and other parts of the ecosystem. The effect of intensification on the amount of land under cultivation is more complex because it depends on accompanying policies, factor markets, and the spatial and temporal scale of analyses. The impact of these feedbacks and indirect effects on land conversion is relatively well studied, but they may also shape the impact of intensification on other environmental outcomes. A review of the literature helps organize existing results and suggests potential approaches to mitigating the environmental costs of agricultural intensification. Further research is needed to understand causal mechanisms and inform policies designed to meet production goals while minimizing environmental costs.